2013
DOI: 10.1371/journal.pone.0074289
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity and Plasticity in a Sound-Evoked Male-Male Interaction in Drosophila

Abstract: During courtship, many animals, including insects, birds, fish, and mammals, utilize acoustic signals to transmit information about species identity. Although auditory communication is crucial across phyla, the neuronal and physiologic processes are poorly understood. Sound-evoked chaining behavior, a display of homosexual courtship behavior in Drosophila males, has long been used as an excellent model for analyzing auditory behavior responses, outcomes of acoustic perception and higher-order brain functions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 40 publications
7
52
2
Order By: Relevance
“…Previous reports described courtship song-induced chaining behavior between males (36)(37)(38). In our assay, we did not observe this behavior.…”
Section: Discussioncontrasting
confidence: 77%
“…Previous reports described courtship song-induced chaining behavior between males (36)(37)(38). In our assay, we did not observe this behavior.…”
Section: Discussioncontrasting
confidence: 77%
“…Dnlg2-deficient flies showed a significantly lower chance of male–male courtship, which might be caused by their larger interindividual distance (Figure 6). It has been shown that CSs stimulate the formation of courtship chains (92, 93) and especially the inter-pulse interval of CSs has been identified as a critical factor for species recognition and attractiveness (20, 94), an alteration in song production might also lead to the chaining phenotype. Since dnlg2 KO17 -mutant males produced songs with significantly prolonged inter-pulse intervals (Figure 6C), complete absence of chaining behavior could also have been a consequence of less attractive songs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that artificial courtship songs dramatically accelerate the chaining behavior of male flies, a typical homosexual courtship behavior in a single‐sex group situation (Eberl et al, ; Yoon et al, ). Female flies, in contrast, gradually decrease their locomotor activity and finally accept a courting male upon exposure to a courtship song (Crossley et al, ).…”
Section: Discussionmentioning
confidence: 99%